Complex Camptosynpolydactyly and Mesoaxial synostotic syndactyly with phalangeal reduction are allelic disorders. Issue 6 (4th April 2016) - Phadke, Shubha R.; Kar, Anjana; Bhowmik, Aneek Das; Dalal, Ashwin
Abstract : Complex Camptosynpolydactyly is an autosomal recessive disorder characterized by complex hand deformities described earlier by us in a consanguineous family. We report on identification of mutations in BHLHA9 gene in this condition. Our results indicate that Complex Camptosynpolydactyly and Mesoaxial synostotic syndactyly with phalangeal reduction (MSSD) are likely to be allelic disorders. © 2016 Wiley Periodicals, Inc.